The new WTO Investment Facilitation for Development Agreement - Karl P. Sauvant (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
On July 6, 2023, 112 WTO members concluded text negotiations on an Investment Facilitation for Development Agreement. This Perspective outlines its contents, identifies its benefits and suggests further actions that should be taken.
Keywords: 330